2015
DOI: 10.1002/ece3.1694
|View full text |Cite
|
Sign up to set email alerts
|

Feather corticosterone reveals stress associated with dietary changes in a breeding seabird

Abstract: Changes in climate and anthropogenic pressures might affect the composition and abundance of forage fish in the world's oceans. The junk‐food hypothesis posits that dietary shifts that affect the quality (e.g., energy content) of food available to marine predators may impact their physiological state and consequently affect their fitness. Previously, we experimentally validated that deposition of the adrenocortical hormone, corticosterone, in feathers is a sensitive measure of nutritional stress in seabirds. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 72 publications
(149 reference statements)
2
21
0
Order By: Relevance
“…Although nestling feather CORT is strongly correlated with environmental conditions during development (e.g. Harms et al ., 2010; Lodjak et al ., 2015; Will et al ., 2015), site- and nest-specific factors can still confound the environment–stress relationship (Fairhurst et al ., 2012; Lodjack et al ., 2015). We did not find a significant influence of either hatch order or number of siblings on feather CORT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although nestling feather CORT is strongly correlated with environmental conditions during development (e.g. Harms et al ., 2010; Lodjak et al ., 2015; Will et al ., 2015), site- and nest-specific factors can still confound the environment–stress relationship (Fairhurst et al ., 2012; Lodjack et al ., 2015). We did not find a significant influence of either hatch order or number of siblings on feather CORT.…”
Section: Discussionmentioning
confidence: 99%
“…Feather corticosterone measurements allow for direct comparison of long-term nestling stress levels between different breeding habitats, where variations in nutrition, contamination, predation and parental attendance may affect chronic chick stress even if no outward physical differences are apparent (Bortolotti et al ., 2009; Harms et al ., 2010). Recent laboratory and field studies have demonstrated that chronic nutritional stress affects feather corticosterone levels in both captive and free-living seabirds (Patterson et al ., 2015; Will et al ., 2015), indicating that feather corticosterone is an appropriate metric for evaluating effects of stressors on chick development.…”
Section: Introductionmentioning
confidence: 99%
“…These impacts can be beneficial, reducing energy expenditure, improving body condition and increasing breeding performance (e.g., Auman et al., ; Flack et al., ). However, when the novel diet replacing natural foods is of poorer quality, this can cause nutritional stress (Will et al., ), reduce nestling growth, both fledgling (Österblom, Casini, Olsson, & Bignert, ) and adult body mass (Rosen & Trites, ), and also be linked to population declines (Kitaysky, Kitaiskaia, Piatt, & Wingfield, ).…”
Section: Introductionmentioning
confidence: 99%
“…In avian biology the technique of measuring stress hormones, glucocorticoids, in feathers is of particular interest as many species grow different groups of feathers at different times of the year. This feature of feathers makes them potentially valuable as indicators of physiological status during life stages when birds are inaccessible to researchers (e.g., Orben et al, ; Ramos, Llabrés, Monclús, López‐Béjar, & González‐Solís, ), over long periods of time (e.g., Fairhurst, Bond, Hobson, & Ronconi, ; Will, Kitaiskaia, & Kitaysky, ), or to assess the response of an individual to conditions over time (e.g., Ganz, Jenny, Kraemer, Jenni, & Jenni‐Eiermann, ; Will et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work on these same individuals showed that rhinoceros auklets experience no ontogenetic patterns in the circulation of corticosterone in plasma, or temporal trends in the concentration of corticosterone in feathers (Figure , Will et al, ). In free‐living individuals raised by their parents, temporal patterns of corticosterone deposition varied both by colony and by year and were associated with diet composition rather than age of the bird (Will et al, ). Due to limitations in detectability of our LC‐MS/MS method, optimized for a suite of steroids, we needed to use whole feathers, and sometimes combined several feathers in the same sample, to have sufficient concentrations.…”
Section: Introductionmentioning
confidence: 99%